Loss Mechanisms in High Efficiency Polymer Solar Cells. Issue 4 (10th December 2015) - MacKenzie, R. C. I.; Balderrama, V. S.; Schmeisser, S.; Stoof, R.; Greedy, S.; Pallarès, J.; Marsal, L. F.; Chanaewa, A.; von Hauff, E.
Abstract : Performance losses and aging mechanisms are investigated in state‐of‐the‐art PTB7:PC70 BM solar cells. Inverted devices incorporating a vanadium pentoxide (V2 O5 ) top contact have efficiencies of 8%. After aging the unencapsulated devices, no changes are observed in the open circuit voltage ( V oc ) or short circuit current ( J sc ); however, the fill factor (FF) drops from 0.7 to 0.61. An s‐shape initially appears in the J – V curve after aging, which can be reduced by cycling through the J – V curve under illumination. This is discussed in context of the redox properties of V2 O5 . With impedance spectroscopy, it is demonstrated that changes to the contact interfaces are completely reversible and not responsible for the performance loss. Intensity modulated photocurrent spectroscopy combined with device modeling reveals that the loss in FF is due to trap formation in the active layer. Additionally it is observed that the performance of pristine devices is limited by optical absorption in the thin active layer and the build‐up of space charge which hinders carrier extraction. Abstract : Air stable PTB7:PC70 BM solar cells with efficiencies of 8% are demonstrated. The device employs a V2 O5 anodic transport layer. Impedance spectroscopy is applied to confirm that the device contact interfaces in this architecture are stable under ambient conditions. Intensity modulated photocurrent spectroscopy is used to model the optoelectronic response of solar cell active layer as a function of aging.